Perancangan Mesin Perajang Singkong - Mustamin, Mustamin; Hasbi, Muhammad; Imran, Al Ichlas (Teknik Mesin Universitas Halu Oleo, 2019)
The purpose of the study was to determine the shaft design, knowing the pulleys and belts to be used and to determine the design of the blade of the cassava chopper machine. The procedure in the design of cassava chopper by using autocad is to prepare the tools and materials to be used; Power planning by calculating the total moment of inertia, calculating the acceleration of the motor, calculating the speed of the rotation angle; Axle planning by calculating the torque moment, calculating the allowable shear stress, calculating the shaft diameter and calculating the shear stress received; Belt and Puli planning is calculating the linear velocity of the belt and calculating the length of the belt and the planning of the Blade which is calculating the compressive strength, calculating the shear strength and calculating each blade style then drawing a cassava chopper. Based on the results of the analysis and discussion in this study it can be concluded that the driving motor power in cassava delivery is 0.698 kW, the shear stress that occurs on the shaft is 1.648 N/mm2, the required belt length is 1513.409 mm with distance axle axis 634.689 mm and compressive strength on the slicing knife are 1.206 N with shear stress 0.0038 N/mm2.Keywords: Twisting moment, shear stress, power, drive motor, shaft, pulley, belt.